National Health Service Bill
1946-04 1946 1940s 10 pages - 9 - APPENDIX to Para. 1 - supra. The following is evidence of the support given by the voluntary hospitals to the conception of a co-ordinated National Health Service, regionally planned. (a) In 1937, the Sankey Commission appointed by the British Hospitals Association, first advocated regional organisation of voluntary hospital services and forecast the desirability of co-ordination of these services with those of the local authorities. (b) Subsequently the Association has vigorously supported the policy of the Nuffield Provincial Hospitals Trust to bring about co-operation with local authorities. (c) In 1942, the Association considered its post-war hospital policy and, inter alia, adopted the following principle: That the facility of hospital treatment ought to be available to every citizen regardless of his financial position. (d) In July, 1944, the Association published a memorandum containing its views on the White Paper on the National Health Service presented by the Coalition Government and therein unequivocally supported the objective of the White Paper, while criticising certain of the methods by which it was proposed that objective should be attained. (e) On 18th March, 1946, the Association published a plan for a National Hospital Service (attached herewith). 292/847/4/19